Effect of Different Feeding on Feed Conversion and Growth of Common Carp (Cyprinus carpio) in Floating Net Cage Culture at Jatiluhur Dike - N.B.P Utomo; F. Kumalasari; I. Mokoginta (Jurnal Akuakultur Indonesia)
This experiment was conducted to evaluate the effectiveness of two feeding methods commonly used in cage culture of carp Cyprinus carpio at Jatiluhur Lake, Purwakarta. Common carp in mean weight of 24.29±4.29 gram were reared in floating net cage 7×7×3 m3, for 70 days rearing.  Fish were fed on a commercial diet containing 30% protein at 5 times daily.  Experimental treatment was feeding technique, i.e., by 6% of body weight, and at satiation for the second treatment.  The results showed that the application of "at satiation feeding method" was more effective than "fixed method" (6% of body weight) indicating with food conversion ratio of 1.86 versus 1.91. Production of fish fed on the diet using at satiation method for 70 days was 1,241 kg/cage.